Management practices for postdural puncture headache in obstetrics: a prospective, international, cohort study. (December 2020) - Gupta, Anil; von Heymann, Christian; Magnuson, Anders; Alahuhta, Seppo; Fernando, Roshan; Van de Velde, Marc; Mercier, Frédéric J.; Schyns-van den Berg, Alexandra M.J.V.; ,; Casier, Isabelle; Bryon, Bart; Soetens, Filiep; et al.
Abstract: Background: Accidental dural puncture is an uncommon complication of epidural analgesia and can cause postdural puncture headache (PDPH). We aimed to describe management practices and outcomes after PDPH treated by epidural blood patch (EBP) or no EBP. Methods: Following ethics committee approval, patients who developed PDPH after accidental dural puncture were recruited from participating countries and divided into two groups, those receiving EBP or no EBP. Data registered included patient and procedure characteristics, headache symptoms and intensity, management practices, and complications. Follow-up was at 3 months. Results: A total of 1001 patients from 24 countries were included, of which 647 (64.6%) received an EBP and 354 (35.4%) did not receive an EBP (no-EBP). Higher initial headache intensity was associated with greater use of EBP, odds ratio 1.29 (95% confidence interval 1.19–1.41) per pain intensity unit increase. Headache intensity declined sharply at 4 h after EBP and 127 (19.3%) patients received a second EBP. On average, no or mild headache (numeric rating score≤3) was observed 7 days after diagnosis. Intracranial bleeding was diagnosed in three patients (0.46%), and backache, headache, and analgesic use were more common at 3 months in the EBP group. Conclusions: Management practices vary between countries, but EBP was more often used in patients with greater initial headache intensity. EBP reduced headache intensity quickly, but about 20% of patients needed a second EBP. After 7 days, most patients had no or mild headache. Backache, headache, and analgesic use were more common at 3 months in patients receiving an EBP.